ICSID 2018 Annual Report - International Centre for Settlement of Investment Disputes (Washington, DC, 2018)
Over more than five decades, ICSID has firmly established itself as the facility of choice for investor-State dispute settlement, having administered more than 70% of all known cases. Demand for the Centre’s services continues to increase, demonstrating the importance of its role. In FY2018 ICSID registered 57 new cases, the highest number in ICSID’s history. A full analysis of the cases is published in the ICSID Caseload — Statistics every six months and is summarized in Chapter 3 of this report.